The influence of applied current density on microstructural, magnetic, and morphological properties of electrodeposited nanocrystalline ni–co thin films - Saraç, Umut; Baykul, M. Celalettin; Uguz, Yasin; Saraç, Umut (Springer, 2015)
Electrodeposited Ni–Co nanocrystalline thin films were grown onto indium tin oxide (ITO)-coated glass substrates from an electrolyte consisting of their sulfate salts and boric acid without stirring at ambient temperature. The effect of applied current density on the microstructural, compositional, magnetic, and morphological properties was investigated using different characterization techniques such as X-ray diffraction (XRD), energy dispersive X-ray (EDX) spectroscopy, vibrating sample magnetometer (VSM), and scanning electron microscopy (SEM). It was observed that the Ni content within the films increases as the applied current density increases. X-ray diffraction (XRD) analyses of Ni–Co films showed the formation of single phase face-centered cubic (FCC) structure and <111>crystallographic orientation. Morphological characterizations revealed that the applied current density affects the surface morphology of the films. The film electrodeposited at high current density has smaller grains than those prepared at lower current densities. Magnetic measurements showed that the coercivity field and remanence ratio of the films decrease as the applied current density increases. Consequently, Ni–Co thin films exhibited different microstructural, compositional, magnetic, and morphological properties according to current density applied during electroplating process.
Keywords: Electrodeposited Ni–Co thin films; Morphological properties; Magnetic characterization; Microstructural properties; Current density